Contours of Coherence in Rabbinic Judaism : Volume 1 - Neusner, Jacob, (Biblical Studies, Ancient Near East and Early Christianity - Book Archive 2000-2006., 2005)
This book shows that the disputes that characterize Rabbinic writings in the formative age underscore the coherence of Rabbinic Judaism. It is in three separate monographs. The first shows that disagreements concern secondary and tertiary issues. They therefore reinforce the primary norm by identifying as moot only trivial details. The second demonstrates, alternatively, that Halakhic disputes articulate unresolved conflict over generative principles. Sometimes, in the presentation of topics of the law, disputes not only indicate the range of consensus but bring to expression conflicting alternatives, theories that claim equal validity but contradict one another. Third, in some presentations of the law and in all presentations of theology where disputes occur, disputes simply gloss details in the application of accepted principles. They form a part of the exercise of legal or theological exegesis, filling in gaps with alternative facts. The print edition is available as a set of two volumes (9789004142312).